Effects of Soybean Gums and Soybean Soapstocks on Weanling Pig Growth Performance, Fecal Dry Matter, and Apparent Total Tract Digestibility of Dry Matter - Katelyn N. Gaffield; Robert D. Goodband; Joel M. DeRouchey; Mike D. Tokach; Jason C. Woodworth; Gordon Denny; Carmen Slipher; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
Soybean processing by-products, such as gums and soapstocks, may be added back to soybean meal during processing, but it is unclear how they may impact pig growth performance. There is potential for these by-products to serve as an affordable energy source for swine due to their residual oil content. A total of 350 pigs (Line 241 × 600, DNA; initially 11.7 ± 0.05 lb) were weaned at approximately 19 d of age and used in a 42-d experiment. At weaning, pigs were randomly assigned to pens and pens were allotted to one of five dietary treatments. There were five pigs per pen and 14 pens per treatment. Diets were fed in three phases: phase 1 from weaning to d 11, phase 2 from d 11 to 23, and phase 3 from d 23 to 42. Treatments included a control diet containing soybean meal with no added soybean by-products. Two additional diets contained gums or soapstocks at 4% of the soybean meal level in the diet. Another treatment diet contained soybean meal with 2% added soybean gums and 2% added soybean soapstocks. Lastly, a negative control contained 4% less soybean meal with no added by-products to have equal protein from soybean meal as the diets with added gums or soapstocks. Feces were collected on d 11 and d 23 from three pigs per pen to determine fecal dry matter (DM). Fecal samples on d 23 were used to determine apparent total tract digestibility (ATTD) of DM. From d 0 to 11 (phase 1) and d 11 to 23 (phase 2), there was no evidence of differences (P > 0.10) for any growth response criteria. From d 23 to 42 (phase 3), feeding soybean meal with added gums increased (P = 0.053) ADG. However, there was no evidence for differences (P > 0.10) in ADFI or F/G. For the overall experimental period (d 0 to 42), there was no evidence of differences (P > 0.10) due to dietary treatment for ADG, ADFI, or F/G. Fecal DM was approximately 19% on both d 11 and 23 and was not affected (P > 0.10) by treatment. There was an interaction (P = 0.019) between soybean gum and soapstocks for the ATTD of DM. When adding 4% gums to the diet, there was an improvement in the ATTD of DM; however, there was no evidence of difference when adding 4% soapstocks or 2% gums and 2% soapstocks to soybean meal compared to the control. These data suggest that adding soybean processing by-products had minimal effects on nursery pig growth performance. However, there is a potential for improved ADG in the late nursery period when soybean meal containing added gums is included in the diet.
Keywords: fecal dry matter; gums; nursery pigs; soapstocks; soybean by-products